Urgensi Hukum Positif Penghapusan Kekerasan Seksual (PKS) di Indonesia sebagai Langkah Penerapan Sustainable Development Goals (SDGs) [The Urgency of the Sexual Violence Eradication Positive Law in Indonesia as the Implementation of Sustainable Development Goals (SDGs)] - Brayent Vivaldi Filemonia; Nicolette Princie Karensa Kusuma; Hetty Antje Geru (Universitas Pelita Harapan, 2021)
The draft law of Sexual Violence Eradication has stolen attentions from all classes of societies. The increase in sexual violence cases in Indonesia have become an “alarm” to bring a positive law into the action as the form of decisive actions from the government to protect its citizens as soon as possible. On the other side, positive law was formed as one of the efforts for the implementation of international organization values. It was explained by the United Nations through its Sustainable Development Goals (SDGs) program. The value promotion process from the international organization level to the domestic level is an action that can be explained by the Neoliberalism theory, where states as rational actors will definitely consider cooperation with other actors in order to achieve its interests. In this context, Social Violence Eradication positive law is the form of Indonesia’s responsibility and commitment towards the SDGs. Bahasa Indonesia Abstract: Rancangan Undang Undang Penghapusan Kekerasan Seksual telah menyita perhatian dari berbagai kalangan masyarakat. Peningkatan jumlah kasus kekerasan seksual di Indonesia menjadi “alarm” bagi negara untuk segera menghadirkan hukum positif sebagai wujud tindak tegas pemerintah dalam melindungi masyarakatnya. Di sisi lain, hukum positif sendiri dibentuk sebagai salah satu upaya implementasi dari nilai-nilai organisasi internasional, yakni Perserikatan Bangsa-Bangsa yang sejalan mengenai penghapusan kekerasan seksual. Hal tersebut dituangkan PBB melalui program Sustainable Development Goals-nya. Proses promosi nilai-nilai dari organisasi internasional ke ranah domestik ini merupakan suatu upaya yang dapat dijelaskan dengan teori neoliberalisme, dimana negara sebagai aktor rasional pasti akan mempertimbangkan kerjasama dengan aktor-aktor lain demi mencapai kepentingannya. Dalam konteks ini, hukum positif penghapusan kekerasan seksual merupakan bentuk tanggung jawab negara terhadap masyarakat sekaligus bentuk komitmen Indonesia terhadap SDGs PBB.